An integrated approach to measure hunting intensity and assess its impacts on mammal populations. Issue 11 (4th October 2020) - Dobbins, Michael; Sollmann, Rahel; Menke, Scot; Almeyda Zambrano, Angelica; Broadbent, Eben
Abstract: Unsustainable hunting of wildlife is one of the greatest threats to diverse and healthy forests, yet our understanding of hunting activity is limited by our methods of accurately identifying its intensity and distribution. Several methods have been used to quantify hunting in past studies (e.g. interviews, ranger patrols and camera traps). However, none of these alone have been able to produce precise spatiotemporal measures of hunting activity. In this study, we used a new method to detect hunters through passive acoustic monitors and developed an integrated approach to measure hunting activity while simultaneously assessing its impacts on mammal populations using camera traps. We applied a hierarchical community occupancy model that accounted for the imperfect detection of species on data from 45 trap locations, surveyed from January to June 2018, to investigate the impacts of spatial variation and intensity in hunting pressure on mammal species richness and occurrence in four protected areas in southern Belize. We developed spatiotemporally explicit indices of hunting activity separately from camera trap and acoustic monitor data and used a Bayesian model selection framework to identify predictors of site occurrence for individual species and three functional groups: carnivores, herbivores and omnivores. We found that camera traps under‐detected hunting activity in the region by 939% compared to acoustic monitors. Consistent with our predictions, hunting intensity was negatively correlated with site‐level species richness, with an average decrease in richness of 31% across its range of variation. Occurrence patterns for the three functional groups were also negatively associated with hunting intensity. Often the target of hunters, herbivores, displayed the strongest negative response to hunting, while omnivores were least affected. Synthesis and applications . Unsustainable hunting of wildlife is a global phenomenon with wide‐ranging implications for ecological communities, especially mammals. Our study highlights mammal sensitivity to increasing hunting pressure at the community and species level and emphasizes the necessity for developing robust tools to accurately monitor hunting activity, while also providing a flexible framework for simultaneously assessing hunting and its impacts on mammal communities. Abstract : Unsustainable hunting of wildlife is a global phenomenon with wide‐ranging implications for ecological communities, especially mammals. Our study highlights mammal sensitivity to increasing hunting pressure at the community and species level and emphasizes the necessity for developing robust tools to accurately monitor hunting activity, while also providing a flexible framework for simultaneously assessing hunting and its impacts on mammal communities. Editor's Choice